Characterization of prokaryotic plankton community structure in the Southern East China Sea using combined 16S-rDNA and 16S-rRNA - Yi-Ting Chang; Po-Yu Liu; Feng-Hsun Chang; Fuh-Kwo Shiah; Chih-hao Hsieh; Hsiao-Pei Lu (Scientific Reports)
Abstract Prokaryotic plankton play a crucial role in marine biogeochemical processes, but their activities can vary significantly among different taxonomic groups. To capture the active part of the communities, both 16S rDNA (genome-level) and 16S rRNA (transcript-level) data were generated in this study to investigate the diversity and activity of prokaryotic plankton in the southern East China Sea. A total of 120 high-throughput sequencing datasets were generated, representing 60 communities sampled seasonally from four water layers along a coastal to pelagic transect. The rRNA:rDNA ratio was used to assess cellular activity for each taxon. The analysis revealed distinct ASVs (amplicon sequence variants) for rDNA and rRNA, with only 12% to 52% overlap in local communities. The taxonomic compositions differed: rDNA was dominated by the archaeal class Nitrososphaeria and the bacterial class Acidimicrobiia, while rRNA was dominated by Alphaproteobacteria, Gammaproteobacteria, and Bacteroidia. ASVs belonging to different classes showed different ranges of rRNA:rDNA ratios, with copiotrophic prokaryotic clades possibly having higher rRNA:rDNA ratios and oligotrophic prokaryotic clades having lower rRNA:rDNA ratios. For example, Gammaproteobacteria, Bacteroidia, Marinimicrobia, and Dehalococcoidia had ratios greater than 1, whereas Alphaproteobacteria, Acidimicrobiia, Planctomycetes, and Nitrososphaeria had ratios less than 1. Despite these differences, rDNA and rRNA equally captured spatial and temporal variations in community structure. Significant community changes were detected across seasons, but the underlying environmental drivers were different for rDNA and rRNA. This study highlights the importance of combining rDNA and rRNA data for a comprehensive understanding of the diversity and activity of marine prokaryotic plankton.